2016
DOI: 10.1007/s00464-016-5185-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting opportunities to increase utilization of laparoscopy for colon cancer

Abstract: There are patient, provider, and hospital characteristics that can be identified preoperatively to predict who will undergo surgery for colon cancer using laparoscopy. However, additional patients may be eligible for laparoscopy based on patient-level characteristics. These results have implications for regionalization and increasing teaching of MIS. Recognizing and addressing these variables with training and recruiting could increase use of minimally invasive approaches, with the associated clinical and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…However, aspects of our results agree with previously published studies for improving outcomes in general for rectal cancer resection. A greater likelihood of laparoscopy in younger, less comorbid patients was found, which is an expected results; these factors have been widely seen in studies for colorectal cancer and described as a predictor of laparoscopy in colon cancer, but not previously for rectal cancer (40)(41)(42). In our study, surgeon specialty was an important predictive factor of laparoscopy, with colorectal surgeons 20% more likely to approach rectal cancer laparoscopically than general surgeons.…”
Section: Discussionsupporting
confidence: 83%
“…However, aspects of our results agree with previously published studies for improving outcomes in general for rectal cancer resection. A greater likelihood of laparoscopy in younger, less comorbid patients was found, which is an expected results; these factors have been widely seen in studies for colorectal cancer and described as a predictor of laparoscopy in colon cancer, but not previously for rectal cancer (40)(41)(42). In our study, surgeon specialty was an important predictive factor of laparoscopy, with colorectal surgeons 20% more likely to approach rectal cancer laparoscopically than general surgeons.…”
Section: Discussionsupporting
confidence: 83%
“…11 In a study that included 24,245 elective colon cancer resections from the Premier Hospital Database from 2009 to 2014, Keller et al observed that higher surgeon volume, colorectal surgeons, and larger hospital size were independently associated with a laparoscopic approach. 14 Outside of the United States, Doumouras et al 29 evaluated variation in the utilization of a laparoscopic approach for colon cancer at the neighborhood level in Ontario, Canada. Including 9969 patients across 516 neighborhoods, the authors identified 74 ''coldspot'' and 75 ''hot-spot'' neighborhoods.…”
Section: Relation To Other Studiesmentioning
confidence: 99%
“…Years in practice was highly correlated with surgeon age (R 2 ¼ 0.912) and characterized as <5, 5 to 9, 10 to 14, 15 to 19, 20 to 24, and !25 years. Annual colectomy volume was characterized as very low (<10), low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), medium , and high (!45) based upon approximate quartile cut-offs and calculated for each calendar-year to account for fluctuation in volume over time. Similarly, annual MIS colectomy volume was characterized as very low (<10), low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), medium (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and high (!40).…”
Section: Surgeon Factorsmentioning
confidence: 99%
“…Advancements include incorporating geriatric-specific assessments and outcomes of importance, along with evidence focused specifically on older adults with colorectal cancer to aid treatment planning. One example is the rising technical capacity and availability of advanced minimally invasive surgery and therapeutic endoscopy [ 49 , 50 ]. These techniques include laparoscopic surgery, transanal local excisions with advanced platforms, and advanced endoscopic techniques including endoscopic submucosal dissection and full thickness resection [ 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: How Should the Evolution Of Treatment Options Impact Screening Recommendations?mentioning
confidence: 99%